Identification of key proteins in host–pathogeninteractions between Mycobacterium tuberculosis and Homo sapiens: A systematic network theoretical approach - Ram Nayan Verma (Healthcare Analytics, 2022)
Tuberculosis (T.B.) is an infectious disease caused primarily by the bacterial pathogen Mycobacterium tuberculosis (Mtb) in humans. The emergence of various drug-resistant Mtb strains threatens to disrupt worldwide attempts to control the infection. The state of disease can be attributed to the host–pathogen protein interaction network. Hence in this study, we have analyzed the protein interaction network at the intra-species level, i.e., within Mtb using the Louvain community detection and at the inter-species level, i.e., between human and Mtb proteins. We observed a higher inter-connectedness in the intra-species protein network as compared to the inter-species network. This reflects a critical role of protein interaction network modulation during host–pathogenesis conditions. After analyzing 269 Mtb proteins and 2287 human proteins using the interlog approach, we observed a total of 640 host–pathogen protein interaction pairing involving 120 humans and 90 Mtb proteins. The H.P.I.s were filtered using functional protein annotations and publicly available experimental results. In the Mtb PPI network, Rv1286, Rv0462, Rv2215, Rv3559c, Rv3504, and Rv3523 are associated as a motif (a governing unit in a network) and identified as key proteins. This interaction network will help researchers better understand host–pathogen protein–protein interactions, as well as shed light on how Mtb interacts with its host.